Helicobacter pylori colonisation and eczema - Herbarth, Olf (BMJ Group, 2007)
The hygiene hypothesis postulates that the increase in atopic diseases may in part be due to diminished exposure to microorganisms. But it is unknown which type of infection does render protection. An epidemiological study was conducted in Leipzig, Germany, and its rural county, involving 3347 school starters. Two types of infection were considered: (1) gastrointestinal colonisation (Helicobacter pylori detection using in vivo [(13)C] urea breath test) and (2) respiratory infections (physician‐diagnosed lower (bronchitis) and upper (common cold) respiratory infections). H pylori colonisation was selected because it is very common and plays an important role in gastrointestinal disorders. Atopic eczema was selected as the (allergic) target variable because of its high frequency in the age of the study participants. The results, adjusted for relevant confounders, showed a significant inverse association between H pylori infection and eczema (adjusted odds ratio (aOR) = 0.31, p = 0.006) in children not predisposed to atopy. In contrast, bronchitis increased the risk of eczema (aOR = 1.98, p<0.001). Bacterial digestive tract colonisation (infection) seems to protect against eczema in comparison with the effect of respiratory tract infections. The hygiene hypothesis may be better explained when gastrointestinal and respiratory infections are subtly differentiated.